The sliding of the signified: multimodal sign operations in a youth-created experimental digital video. (August 2018) - Ranker, Jason
In this article, the author presents a multimodal discourse analysis of a digital video composed by five students (ages 11–12) in an urban, public-school classroom. The focal mockumentary video is distinctive in that it is difficult to interpret and has an artistic quality that turns the process of meaning-making back on itself, resisting the very idea of a single, determinable meaning. He examines this phenomenon as the sliding of the signified in the students' video (as multimodal discourse), focusing on the ways in which the students tapped into discursive agencies that rupture meaning-making. In particular, he analyzes how visual and spoken signifiers are related or coordinated with one another across the film in the creation of multimodal discursive effects such as floating signifiers, networks of metonymic potential, and signifier condensation complexes. This study thus offers conceptualizations of multimodal discursive units that can be used to interpret and analyze the interactions of visual and spoken signifiers in films and digital videos.